Some Problems with the Investigation of Noninferiority in Meta-analysis - Witte, S.; Victor, N. (Methods of Information in Medicine, 2004)
Objectives: Noninferiority trials have become commonplace in recent years. Like individual clinical trials, meta-analyses can also investigate noninferiority. However, certain important topics have to be considered.Methods: The proposed methods in this paper have their origin in the framework of noninferiority trials and meta-analyses. This paper can therefore be seen as a combination of both fields. Two issues are highlighted in the paper; difficulties in the choice of delta for a noninferiority meta-analysis leading to different deltas and methods for meta-analyses with different analysis sets, based on the full-analysis set with the intention-to-treat principle or the per-protocol population. Analytical methods, sensitivity analyses, meta-regression, and a bivariate method are introduced. The proposed graphical presentations support the analytical results.Conclusion: The confidence interval approach using meta-regression or bivariate methods is appropriate using both analysis sets for meta-analyses investigating noninferiority.
Keywords: Meta-analysis; equivalence; choice of delta; population sets